Sistem Informasi Manajemen Bengkel Beserta Peralatannya: Studi Kasus Implementasi Aplikasi Berbasis Web Sistem HO PT.PAL INDONESIA - Alif Syifa’ul Qulub; Umi Chotijah (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Effective and efficient workshop management is a crucial element in the shipbuilding industry to ensure smooth production processes and quality final results. In an effort to increase efficiency and productivity, this research optimizes workshop management from equipment to monitoring project work on this system. Especially in the HO (Hull Outfitting) system at PT. PAL INDONESIA. The case study method was used to collect data from field observations, interviews with relevant personnel and analysis of documentation related to application implementation. This application facilitates more detailed real-time monitoring of workshop activities, allowing managers to quickly identify and resolve operational problems and take necessary corrective actions. The use of this application also aims to improve equipment and material management with more efficient scheduling and better integration between various departments. Implementing the HO (Hull Outfitting) system in applications also provides additional benefits, such as more integrated and comprehensive project management, better monitoring of the condition of workshop equipment, and reduced risk of errors and delays. With a web-based application, the equipment calibration and maintenance process is more structured, transparent and responsive to changes. These findings underline the importance of information technology in supporting the optimization of workshop management and increasing productivity in the shipbuilding industry.